Seroprevalence and epidemiological characteristics of HDV infection among HBV patients in the Nile Delta, Egypt. Issue 1 (7th October 2021) - Elzefzafy, Wafaa; Soliman, Reham; Saleh, Layla; Mahmoud, Safyia; Makhlouf, Nahed A; Shiha, Gamal; Zaky, Samy
Abstract: The epidemiology of HDV infection worldwide is obscure. Mapping the epidemiology of the infection is highly required, so, we aimed to estimate the prevalence of hepatitis D virus infection among chronic hepatitis B patients and the epidemiological characteristics in the Nile delta in Egypt. This was a prospective observational cross‐sectional study including consecutive chronic hepatitis B patients in the out‐patient clinics at the Egyptian Liver Research Institute and Hospital (ELRIAH) and its satellites in the Nile Delta from January 2016 until August 2018. They were recruited from patients enrolled in Educate, Test and Treat program, which was implemented in 73 Egyptian Villages. Subjects were tested by using HBsAg serological rapid diagnostic tests (RDTs), and then HBV DNA by PCR was done in HBsAg‐positive cases. HDV IgG antibody testing and confirmatory HDV RNA PCR were done. Complete liver functions, abdominal ultrasonography and FibroScan were also performed. The prevalence of HDV was 3.4% using anti‐delta antibody (22/631), and only 8 were positive for HDV RNA (8/22, 36.4%). Overall HDV prevalence using PCR was 8/631(1.27%). HDV‐positive cases were mainly males (68.2%). Eight cases were cirrhotic (36.4%), 3 (13.6%) had HCC and 7 (31.8%) were HBeAg positive. HDV prevalence is low among chronic hepatitis B patients in the Nile delta, Egypt. Screening for HDV IgG is recommended in CHB patients who had cirrhosis, HCC or HBeAg positive.